Sekularisme dalam Pendidikan di Malaysia - Nurul Farhanah Binti Masri (Jurnal Pemikiran Islam, 2022)
The majority of the population of Malaysia is Muslim. However, Islam does not regulate all aspects of state life in this country. The education aspect, for example, is more directed to the western education system and model than the Islamic education system, as well as in the Malaysian state government and political system. The purpose of this study is to classify the idea of secularism that is applied in policy or development in Malaysia, especially in the field of education. This research is a field research, using interviews, observation and documentation as data collection techniques. The results of this study indicate that the Malaysian state has implemented secularism in the government system in Malaysia. This is due to the influence of British colonialism which replaced the model of government based on Malay culture into a democratic system of government, political, social, economic and educational systems. This resulted in the Islamic model slowly starting to be erased, especially in education.AbstrakMayoritas penduduk negara Malaysia menganut agama Islam. Namun tidak semua aspek kehidupan bernegara di negara ini dilaksanakan berdasarkan ajaran islam.  Aspek pendidikan misalnya, sistem pendidikan lebih mengarah pada model dan sistem pendidikan barat dan tidak menganut pada sistem pendidikan Islam, begitu juga dalam sistem pemerintahan dan politik negara Malaysia. Tujuan penelitian ini juga untuk mengklasifikasikan tentang ide sekularisme yang diterapkan dalam kebijakan atau pembangunan di Malaysia khususnya dibidang pendidikan.. Penelitian ini adalah penelitian lapangan (field research) dengan menggunakan metode wawancara, observasi dan dokumentasi sebagai teknik pengumpulan data. Hasil penelitian ini menunjukkan bahwa negara Malaysia telah menerapkan sekularisme dalam sistem pemerintahan di Malaysia. Hal ini disebabkan oleh pengaruh penjajahan Inggris yang menggantikan model pemerintahan yang berbasis pada budaya melayu menjadi sistem demokrasi sistem pemerintahan, politik, sosial, ekonomi dan pendidikan.  Hal ini mengakibatkan secara perlahan model islami mulai terhapus khususnya dalam pendidikan.